2017
DOI: 10.1108/ijmce-06-2017-0045
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring beginning teachers: professional learning for mentees and mentors

Abstract: Purpose-This paper introduces this special issue focusing on the mentoring of beginning teachers which supports the professional learning of not only mentees but also mentors. The paper identifies the varied aims of beginning teacher mentoring programmes, some of the reasons for mentoring and an introduction to the six research papers published in the issue. Design/methodology/approach-The papers in this issue examine different perspectives relating to the mentoring of student teachers and newly qualified teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 3 publications
1
20
0
2
Order By: Relevance
“…The issue of mentorship and its complexities has been discussed extensively in international research (Augustiniene & Ciuciulkiene, 2013;Hagger, McIntyre & Wilkin, 2013;Shanks & Shanks, 2017). In addition, the authors recognise the importance of critically examining the mentor-mentee relationship with specific focus on who this relationship best serves.…”
Section: Supervising Teachers As Mentorsmentioning
confidence: 99%
“…The issue of mentorship and its complexities has been discussed extensively in international research (Augustiniene & Ciuciulkiene, 2013;Hagger, McIntyre & Wilkin, 2013;Shanks & Shanks, 2017). In addition, the authors recognise the importance of critically examining the mentor-mentee relationship with specific focus on who this relationship best serves.…”
Section: Supervising Teachers As Mentorsmentioning
confidence: 99%
“…Formal mentoring programs help establish collegial norms and facilitate the engagement of new teachers in the life of the schools and in the professional learning structures, such as school learning communities (Kutsyuruba, 2012). As Shanks (2017) pointed out, “Mentoring in teacher education often has the dual aims of personal support and professional learning because the mentee receives assistance to assimilate into a new role as well as to develop instructional skills” (p. 159). Better understanding of mentorship programs with teacher education programs could help with transitioning into a mentorship model with early career teachers.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in a recent survey of CTs in Chicago, almost one fifth of CTs indicated that their primary reason for serving as a CT was because it helped them to improve as a teacher (Matsko, Ronfeldt, & Greene Nolan, 2019). This is further supported by a review of mentoring programs for novice teachers in the United Kingdom, where Shanks (2017) finds that mentors, in coaching novices, sometimes engage in the same kinds of critical inquiry and reflection as mentees, creating opportunities for learning for both parties. Thus, we test for lagged effects of serving as a CT on teachers' instructional performance in years after they mentored candidates.…”
Section: Contributions Of the Present Studymentioning
confidence: 92%